1994
DOI: 10.1123/ijsn.4.3.253
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol Supplementation in Racing Cyclists during Extreme Endurance Training

Abstract: This study was undertaken to evaluate the effects of 5 months of α-tocopherol supplementation on physical performance during aerobic exercise training in 30 top-class cyclists. Antioxidative effects of supplementation were also studied. Plasma α-tocopherol concentration increased significantly in the vitamin E-supplemented group, whereas the placebo group showed a trend toward decrease. Physical performance did not improve in the α-tocopherol-supplemented group compared to the placebo group. Heart rates were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 11 publications
8
80
0
Order By: Relevance
“…However, no study has demonstrated improvement in performance after supplementation in non-deficient individuals (34)(35) . Due to α-tocoferol efficiency in reacting with peroxyl radicals, many studies have been conducted with the purpose to evaluate the effect of α-tocoferol supplementation in the LP, caused by oxidative stress induced by physical exercise.…”
Section: Vitamin Ementioning
confidence: 99%
See 2 more Smart Citations
“…However, no study has demonstrated improvement in performance after supplementation in non-deficient individuals (34)(35) . Due to α-tocoferol efficiency in reacting with peroxyl radicals, many studies have been conducted with the purpose to evaluate the effect of α-tocoferol supplementation in the LP, caused by oxidative stress induced by physical exercise.…”
Section: Vitamin Ementioning
confidence: 99%
“…Rokitzki et al (34) have observed that the supplementation promoted lower plasma concentration of CK in response to endurance exhaustive exercise practiced by athletes. Sachek et al (37) verified this effect up to 24 hours after running exercise at 75% VO 2máx in young males, supplemented with 1000 UI/day of vitamin E during 12 weeks.…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, occasional reports of marginal vitamin B 6 and E intake in male athletes 54 . Vitamin intakes in female athletes are typically above the recommendations, but not very much higher than in untrained females 28,30,33,53,[57][58][59][60][61] . Several studies have found low iron 28,30,53,[57][58][59][60][61] , zinc 30,59,62 and copper 28 intakes in both female athletes and controls.…”
Section: Dietary Intake -A Balancing Factor?mentioning
confidence: 99%
“…Plasma LOOHs levels were determined using the FOX 2 method [29] with minor modifications [34]. The FOX 2 test system is based on the oxidation of ferrous ion to ferric ion by various types of peroxides contained within the plasma samples, to produce a colored ferricxylenol orange complex whose absorbance can be measured.…”
Section: Measurement Of Plasma Loohs Levelsmentioning
confidence: 99%